THE ASSESSMENT AND MODELING OF BARRIERS TO INDUSTRY 4.0 IMPLEMENTATION IN THE SUPPLY CHAIN - Pandey A.A.K.; Winston B.P.; Pratap C.S.; Daultani Y. (My University, 2025)
The principles of Industry 4.0 and digitalization include interoperability, virtual applications, distributed systems, real-time capability, service orientation, and modular production. These ideas, which place a significant emphasis on processes, products, and business models, could improve how firms run their operations when combined with supporting technology. To evaluate the supply chain adoption of Industry 4.0, the study combines the FUZZY AHP and PROMETHEE II approaches. The findings indicate that the impediments that have the greatest significance and negatively impact the supply chain's performance include reluctance on the part of supply chain partners, management support, and network and IT infrastructure. © 2023 Computers and Industrial Engineering. All rights reserved.